2014
DOI: 10.1002/rcm.7026
|View full text |Cite
|
Sign up to set email alerts
|

Species‐related difference between limonin and obacunone among five liver microsomes and zebrafish using ultra‐high‐performance liquid chromatography coupled with a LTQ‐Orbitrap mass spectrometer

Abstract: The ESI-HR-MS/MS fragmentation behaviors of limonin and obacunone were investigated for the first time. A qualitative and semi-quantitative method was developed for the in vivo and in vitro metabolic analysis of limonin and obacunone. The results demonstrated that the metabolic processes of limonin and obacunone were different between LMs and zebrafish. However, both of these two parent compounds presented similar metabolic processes in five species of LMs. This was caused by the metabolic difference between m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 40 publications
5
23
1
Order By: Relevance
“…Objectives of this study were to investigate the metabolic profiles of four limonoids (limonin, obacunone, nominin and gedunin) in HLMs using ultra‐high performance liquid chromatography coupled with high‐resolution mass spectrometry (UHPLC/HRMS) and to identify the cytochrome P450 (CYP) enzymes involved in the formation of their metabolites by recombinant human CYP enzymes. In our previous study, one metabolite of limonin and two metabolites of obacunone were tentatively identified, which established the basis for further research . In the present study, based on the accurate HR‐MS/MS data and the proposed MS/MS fragmentation pathways, in total 21 metabolites of the four limonoids were characterized, the possible metabolic pathways proposed and the involved CYPs investigated.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Objectives of this study were to investigate the metabolic profiles of four limonoids (limonin, obacunone, nominin and gedunin) in HLMs using ultra‐high performance liquid chromatography coupled with high‐resolution mass spectrometry (UHPLC/HRMS) and to identify the cytochrome P450 (CYP) enzymes involved in the formation of their metabolites by recombinant human CYP enzymes. In our previous study, one metabolite of limonin and two metabolites of obacunone were tentatively identified, which established the basis for further research . In the present study, based on the accurate HR‐MS/MS data and the proposed MS/MS fragmentation pathways, in total 21 metabolites of the four limonoids were characterized, the possible metabolic pathways proposed and the involved CYPs investigated.…”
mentioning
confidence: 73%
“…At present, limonoids have gained significant importance because of their aforementioned biological activities and the possibility to determine limonoids in rat plasma and human urine . The electron ionization (EI) and atmospheric pressure chemical ionization (APCI) tandem mass spectrometric (MS/MS) fragmentation pathways of limonoid aglycones and ESI‐MS/MS fragmentations of limonoids have been reported . However, few studies about the metabolic profiles of limonoids have been carried out.…”
mentioning
confidence: 99%
“…This is probably caused by metabolic differences between mammals and fish or, more simply, 1 probably cannot be absorbed in zebrafish (cf. cLog P values for 1 and 3 in Table 2) [174]. One year later, a more exhaustive study in human liver microsomes, performed on 2, revealed other metabolites arising from isomerization, hydroxylation, and conjugation with glycine of reduced limonoids, with the latter metabolic pathway being observed for the first time.…”
Section: Metabolic Transformations Of Secondary Metabolitesmentioning
confidence: 96%
“…In 2014, Ren et al [174] carried out a comparative investigation on the metabolism of 1 and 3 in five different species of liver microsomes (human, monkey, dog, rat, and mouse liver microsomes) and in zebrafish through ultra-high performance liquid chromatography (UHPLC) coupled with a high-resolution LTQ Orbitrap mass spectrometer. The ESI-HR-MS/MS fragmentation behaviors of 1 and 3 were investigated for the first time and their metabolic rates were estimated using UHPLC/HRMS.…”
Section: Metabolic Transformations Of Secondary Metabolitesmentioning
confidence: 99%
“…1), a limonoid, is a kind of characteristic secondary metabolite belonging to highly oxygenated triterpenoid derivatives and enriched in citrus fruits [1][2][3], for example the fruit of Evodia rutaecarpa (Juss.) Benth, E. rutaecarpa (Juss.)…”
Section: Introductionmentioning
confidence: 99%